THE EFFECT OF AUDIT LAG, AUDITOR’S REPUTATION, COMPANY SIZE, AND COMPANY GROWTH ON GOING-CONCERN AUDIT OPINION - Ramadhani, Runaily; Anisma, Yuneita; Safitri, Devi (Universitas Tidar, 2024)
The purpose of this study is to test and demonstrate empirically the effects of audit lag, auditor’s reputation, company size, and company growth on going-concern audit opinion. This study is a quantitative study with secondary data sources. The population of this study includes 58 mining companies registered on the IDX in 2017-2021. The samples consist of 25 companies which were selected through a purposive sampling technique. The hypothesis was tested using logistic regression analysis with the IBM SPSS 25 application. According to the logistic regression test, audit lag and company size have a positive impact on going-concern audit opinion. However, neither auditor reputation nor company growth has any effect on going-concern audit opinion.